Ablative Therapies for Central Airway Obstruction - Mahmood, Kamran; Wahidi, Momen M. (Seminars in Respiratory and Critical Care Medicine, 2014)
Central airway obstruction (CAO) is seen in malignant and nonmalignant airway disorders and can lead to significant morbidity and mortality. Endobronchial ablative therapies are used in conjunction with mechanical debridement to achieve hemostasis and restore airway patency. These therapies can be classified into modalities with immediate or delayed effect. Therapies with immediate effect include heat therapies (such as electrocautery, argon plasma coagulation, and laser) and cryorecanalization using a cryoprobe for tissue extraction. These modalities can be used in severe CAO for immediate relief of obstruction. Therapies with delayed effect include cryotherapy, brachytherapy, and photodynamic therapy. These modalities should not be used for acutely symptomatic CAO, and typically require follow-up bronchoscopy for removal of debris from the airway. Multimodality approach typically leads to better outcomes.
Keywords: central airway obstruction; ablative therapy; electrocautery; argon plasma coagulation; airway; laser; cryotherapy; brachytherapy; photodynamic therapy